2017
DOI: 10.5194/acp-17-3133-2017
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the aerosol indirect effect over the Baltic Sea region derived from 12 years of MODIS observations

Abstract: Abstract. Retrieved from the Moderate Resolution Imaging Spectroradiometer (MODIS) on-board the Aqua satellite, 12 years (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) of aerosol and cloud properties were used to statistically quantify aerosol-cloud interaction (ACI) over the Baltic Sea region, including the relatively clean Fennoscandia and the more polluted central-eastern Europe. These areas allowed us to study the effects of different aerosol types and concentrations on macro-and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 33 publications
(32 reference statements)
3
31
0
3
Order By: Relevance
“…By virtue of their large coverage and high spatial and temporal resolution, satellite-borne instruments have become a promising observational tool in studying ACIs. Previous studies using a large amount of satellite data and/or multiple satellite instruments have shown that aerosol particles can affect cloud properties significantly (Krüger and Grassl, 2002;Menon et al, 2008;Sporre et al, 2014;Rosenfeld et al, 2014;Saponaro et al, 2017). Satellite measurements suggest that the CDR tends to decrease with increasing aerosol loading, which is consistent with Twomey's theory (Matheson et al, 2005;Meskhidze and Nenes, 2010;Koren et al, 2005).…”
Section: Introductionsupporting
confidence: 75%
“…By virtue of their large coverage and high spatial and temporal resolution, satellite-borne instruments have become a promising observational tool in studying ACIs. Previous studies using a large amount of satellite data and/or multiple satellite instruments have shown that aerosol particles can affect cloud properties significantly (Krüger and Grassl, 2002;Menon et al, 2008;Sporre et al, 2014;Rosenfeld et al, 2014;Saponaro et al, 2017). Satellite measurements suggest that the CDR tends to decrease with increasing aerosol loading, which is consistent with Twomey's theory (Matheson et al, 2005;Meskhidze and Nenes, 2010;Koren et al, 2005).…”
Section: Introductionsupporting
confidence: 75%
“…Koren et al () previously suggested an enhancement of cloud vertical structure over the North Atlantic due to aerosol loading. Saponaro et al () also found that the lowest CTP corresponds to the highest classes of AI over the Baltic Sea region. This is not evident over three anthropogenic regions but seems true over the adjacent oceans (Figure ), especially ECO and EUO, where the lowest CTP values (highest cloud top height, CTH) correspond to highest classes of AI.…”
Section: Aerosol‐cloud Correlationsmentioning
confidence: 89%
“…The studies by Dusek et al () and Zhang et al () found that particle size is dominant to determine aerosol activation, but many studies demonstrated that the chemical composition is also critical (Almeida et al, ; Ervens et al, ; Lance et al, ; McFiggans et al, ; Nenes et al, ; Wang et al, ). In addition, dynamical or meteorological conditions will strongly affect aerosol‐cloud interactions by changing vertical velocity or wind shear (Gryspeerdt et al, ; Fan et al, ; Koren et al, ; Loeb & Schuster, ; Mauger & Norris, ; Saponaro et al, ; Su et al, ; Tang et al, ; Wang et al, ). Overall, negative correlations are normally found over oceans while positive over land.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of cloud properties to aerosol perturbation is usually used to quantify ACI (Bai et al, 2018; Saponaro et al, 2017), such as the sensitivity of CDNC to aerosol loading (usually expressed by AOD or AI) (e.g., Ban‐Weiss et al, 2014; Grandey & Stier, 2010; Gryspeerdt & Stier, 2012; Ma et al, 2014; Quaas et al, 2008). However, most of these studies were based on instantaneous and/or short‐term observations, and results from such studies may have suffered from meteorological covariation (e.g., Mülmenstädt & Feingold, 2018) or effect of inter‐annual variability (Sekiguchi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%